Cost-effectiveness of analysis serplulimab plus chemotherapy as first-line therapy for PD-L1-positive advanced esophageal squamous cell carcinoma - Zheng, Hanrui; Li, Jiafeng; Wen, Feng; Su, Na (Frontiers in Oncology, 2023)
Objective Our study aimed to evaluate the cost-effectiveness of the addition of serplulimab to chemotherapy (cisplatin and fluorouracil) for programmed death-ligand 1 (PD-L1) positive advanced esophageal squamous cell carcinoma (ESCC) as the first-line treatment in China. Methods A three-state Markov model was established to assess the incremental cost-effectiveness ratio (ICER) for serplulimab plus chemotherapy versus chemotherapy alone. Survival data were extrapolated from the ASTRUM-007 trial, cost data were derived from local sources, and utilities were derived from published literature. Health outcomes were measured as quality-adjusted life-years (QALYs). Sensitivity and probability sensitivity analyses were used to investigate the robustness of the model. Results In the base-case analysis, compared with chemotherapy alone, serplulimab gained an additional 0.16 QALYs with an incremental cost of $29,547.88, leading to an ICER of $184,674.25/QALY. Additionally, the subgroup analyses presented that the ICERs of serplulimab plus chemotherapy were $157,892.50/QALY and $127,996.45/QALY in advanced ESCC patients with 1≤ CPS< 10 and CPS≥ 10, respectively. These ICERs significantly exceeded the Chinese willingness-to-pay (WTP) threshold. The deterministic sensitivity analysis illustrated that the cost of progression-free survival in serplulimab plus chemotherapy group was the parameter with the strongest influence on the ICERs. Conclusion In the Chinese health care system, with 3 times China’s per capita gross domestic product as the WTP threshold, compared with chemotherapy alone, serplulimab combined chemotherapy is not economical for PD-L1-positive advanced ESCC in the first-line setting.